Institutes of civil society in the protection of copyright - BOICHUK Дмитро (Ius Modernum, 2025)
The growing role and multifaceted activities of civil society institutions (CSIs) in the mechanism for protecting copyright and human rights in Ukraine have been studied, which has become particularly relevant in the context of democratic transformations, European integration processes, and the challenges of a full-scale war. The purpose of the article is to study the role, functions and effectiveness of civil society institutions in the mechanism of copyright and human rights protection in Ukraine. The hypothesis of the study is based on the assumption that the active and multifaceted activities of civil society institutions in Ukraine are positively correlated with increasing the effectiveness of the mechanism of copyright and human rights protection, but its potential is limited by systemic problems, which requires the improvement of legal and institutional foundations to ensure the sustainability of their functioning and to strengthen interaction with state bodies. It has been established that CSIs implement polymorphic activities: in the field of copyright – it is educational activity, monitoring of violations (especially in the digital environment), providing legal assistance, participating in advocacy of legislative changes, as well as the specific role of collective management organizations (CMOs); in the field of human rights – monitoring and documenting violations, providing legal assistance, national and international advocacy, shaping public opinion and protecting rights related to creativity and information. The effectiveness of the CSIs is limited by systemic problems: financial and resource constraints, imperfection of legislation, low level of legal culture among the population, difficulties in interaction with state bodies, and challenges of martial law.